PENGARUH MEDIA PEMBELAJARAN VIDEO ANIMASI TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA PESERTA DIDIK KELAS IV SD - Richy Afrindo; Dayu Rika Perdana; Siti Nuraini; Rapani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The problem in this study was the low learning outcomes of grade 4th students of SD Negeri 6 Metro Utara. This study aims to determine the effect of animated video learning media on learning outcomes of Pancasila education. This research method used quantitative research with a quasi-experimental design. The population and sample of the study amounted to 54 students. Determination of the sample used a saturated sample technique. The data collection technique used a test technique in the form of multiple choice questions totaling 25 questions which were carried out twice, namely during the pretest and posttest. The data analysis technique used simple linear regression. The results of the study are that there is an effect of animated video learning media on the learning outcomes of Pancasila education with ???????????????????????? > ???????????????????????? or 25.644 > 4.260.